PENERAPAN E-PUSKESMAS PADA PUSKESMAS TANJUNGPINANG - Satriadi Satriadi; Dwi Septi Haryani (Universitas Dian Nuswantoro Semarang, 2019)
In the era of industrial revolution 4.0 which most of it integrated to the internet, of course technology information nowadays has becomes something that part of out needs for some people even for every one in this world. Every health services in an area of city must be capable to do the best, so the progress in giving health services to society could be so much effective. Health service that easily be found in an area or city is Puskesmas. Most people are often feeling so dissapointed to the activity progress in Puskesmas. However, this has been minimalized through using management information system which found in Puskesmas (e-Puskesmas). This research was held in Puskesmas Tanjungpinang. This research’s purpose is to know the implementation of management information system (e-Puskesmas) in Puskesmas Tanjungpinang. Research method been done by doing obvservation and interview to health service activity that happened in Puskesmas. The result of this research is that management information system implementation in Puskesmas Tanjungpinang not yet fully integrated.